Tanggung Jawab Hukum Jasa pengangkut Limbah dalam Pengelolaan Limbah Medis Padat Rumah Sakit - Anindya Dwita; Mohammad Zamroni (Jurnal Hukum dan Etika Kesehatan, 2021)
Hospitals not only produce ordinary waste, but also produce infectious waste and other medical waste that can interfere with health and is one of the media for the spread of disease. PP PLB3 has stated that every waste producer is obliged to process the waste, if he cannot do it himself, he can hand it over to another party. Not all hospitals in Indonesia have their own waste processing capability, giving rise to the need for hospitals to work together with waste transport services to bring the medical waste they produce to more licensed waste processing services in Java. The transportation activity has a high risk given the characteristics of the waste carried and the risk of environmental pollution caused. In the process of transporting hospital medical waste there is no definite guarantee that in the course of transportation there is no negligence or intentionality of the waste transporter to not dump the solid medical waste he carries. The research method used in this study is a normative juridical method (literature study), namely the method or method used in legal research conducted by examining existing library materials. The approach in this study is the Statute Approach, which is the approach used to examine and analyze laws and regulations relating to legal issues under investigation. The second approach is the Conceptual Approach (conceptual approach) which is an approach that departs from the views and doctrines that develop in law. The government itself has issued a number of rules governing the problem of managing solid medical waste, and in the event of environmental pollution the parties involved are subject to strict liability principles both civil and criminal. Legal protection efforts carried out by hospitals are preventive legal protection efforts by implementing an Environmental Management System, taking precautions in managing solid medical waste internally and improving cooperation agreements with waste transport and processing services